2022
DOI: 10.3389/frhs.2022.852322
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chronic Pain, Resilience and Psychiatric Comorbidity in Canada: A Retrospective, Comparative Analysis

Abstract: ObjectiveChronic pain compromises child and adolescent well-being and development. This study aimed to identify risk factors for chronic pain and exploration of how young people negotiate such risks and express resilience. We hypothesized children and youth with chronic pain would report greater prevalence of mental health disorders than the general population; and those demonstrating greater resilience would demonstrate less psychiatric comorbidity.MethodA retrospective chart review was conducted for all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Our study sample included more females than males, and this difference was especially pronounced within the pediatric sample. Though this is in line with past research 7 and similar female-to-male ratios have been reported in adults 48 and children, 49 this gender bias may also reflect sex-based disparities in research participation, access to health care, and resource utilization among persons living with chronic pain. To limit the number of survey questions and respondent burden, we only asked the participants about their gender, not biological sex.…”
Section: Discussionsupporting
confidence: 89%
“…Our study sample included more females than males, and this difference was especially pronounced within the pediatric sample. Though this is in line with past research 7 and similar female-to-male ratios have been reported in adults 48 and children, 49 this gender bias may also reflect sex-based disparities in research participation, access to health care, and resource utilization among persons living with chronic pain. To limit the number of survey questions and respondent burden, we only asked the participants about their gender, not biological sex.…”
Section: Discussionsupporting
confidence: 89%